The abundance and diversity of the seagrasses in tne northern coast of Tacloban City, Philippines. - Flores, Lourdes Joyce D. (Lourdes Joyce D. Flores, 2018)
The seagrasses of the northern coast of Tacloban City were characterized based on the abundance and diversity by calculating the percentage cover, determination of biomass through quadrat sampling with five 50 m transect line laid that covered five barangays along the northern coast which were Brgy. Anibong, Brgy. Cabalawan, Brgy. Tagpuro, Brgy. San Isidro and Brgy. Kawayan and mapping the extent of the seagrass beds with the use of a GPS and plotted in QGIS. The highest biomass was in Brgy. Cabalawan (94.26 g/meter square DW) while the lowest biomass was in Brgy. Anibong (19.51 g/meter square DW). Only Enhalus acoroides was present in the three barangays (Brgy. Anibong, Brgy. Kawayan and Brgy. San Isidro) and Enhalus acoroides and Thalassia hemprichii in two barangays (Brgy. Cabalawan and Brgy. Tagpuro). The calculated average percent cover which was at 12.13% plus/minus 0.79 is lower than that of the study which was simultaneously conducted along the southern coast of Tacloban City (75.3% plus/minus 5.22). Threats observed on the growth and production of seagrasses were human activities such as fish pens and siltation along the covered barangays in the study site. Proper knowledge on the growth and production of the seagrasses would help in the rehabilitation and management of the seagrasses in the northern coast of Tacloban City.